PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN APLIKASI QUIZIZ DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA KELAS VII DI SMP NEGERI 4 MARISA KABUPATEN POHUWATO - Nurhaliza S. Lamapa; Agil Bahsoan; Imam Prawiranegara Gani; Meyko Panigoro; Abdulrahim Maruwae (Journal of Economic and Business Education, 2025)
This study aims to examine the extent to which the implementation of the Teams Games Tournament (TGT) learning model can improve students' learning outcomes in Social Sciences for Grade VII students at SMP Negeri 4 Marisa, Pohuwato Regency. The TGT model is a cooperative learning strategy designed to improve student engagement through educational games and intergroup competitions. This study employed a Classroom Action Research (CAR) approach conducted over two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The subjects of the study were 23 grade VII students. The instruments used included learning outcome tests, observation sheets, and documentation. Based on the analysis of mastery learning outcomes, the initial observation showed that 43.38% of students achieved the minimum mastery criteria; this increased to 73.91% in the first cycle and 91.30% in the second cycle, indicating a 17.39% improvement.Based on the identified improvement in learning outcomes, it can be concluded that the use of the Teams Games Tournament (TGT) model assisted by the Quizizz application significantly improves students' learning outcomes. Furthermore, this model promotes active student participation in the learning process, fosters group responsibility, and creates a more enjoyable learning environment. In light of these GT model as findings, it is recommended that Social Sciences teachers TGT an alternative for designing interactive and effective learning experiencesconsidered outcomes. Socraf Sciences,